KADER EMPOWERMENT IN EARLY DETECTION OF HIGH RISK PREGNANT WOMEN IN TERATAK BULUH VILLAGE, WORKING AREA OF PUSKESMAS SIAK HULU II, KAMPAR REGENCY, 2022 - LAILIYANA, LAILIYANA; YAN SARTIKA; ELLY SUSILAWATI (KRIDA CENDEKIA, 2022)
The results of the study have proven that in addition to the direct causes, namely bleeding, infection and pre-eclampsia, cases of maternal death are related to the risk factors contained in the Puji Rochyati Score Card (KSPR) and the late factor four. (Widarta, G.D., 2015). The author’s initial survey data in April 2021 in Teratak Buluh Village obtained 2 people (11.1%) of 18 pregnant women who came to visit the pregnant women class including the category of pregnant women with high risk, namely weight less than 45 kg and age above 35 year. Early detection of high-risk pregnancies is very important during antenatal care. The easiest way to detect high-risk pregnancies, including by health cadres, is to use KSPR. This community service activity aims to empower Posyandu cadres in early detection of high-risk pregnant women in the village of Teratak Buluh The working area of the Siak Hulu II Health Center, Kampar Regency. The target of the activity is posyandu cadres in teratak reed village, totaling 25 cadres spread over 6 posyandu. The method of implementing this Community Service activity is to conduct training to cadres on high-risk pregnancy assessment using KSPR, as well as assisting cadres in conducting early detection of high-risk pregnant women. The training was carried out in coordination with the Siak Hulu II Health Center as the person in charge of the program and the Teratak Buluh Village community leader as the person in charge of the area. The results showed that there was an increase in the knowledge of cadres about the assessment of pregnancy risk factors between before and after the training, with an average pretest value of 76.8 to 92.6. The skills of cadres to assess pregnancy risk using KSPR are very satisfactory with an average score above 50, namely 71.72, with a minimum score of 64.29 and the highest score of 85.71. At the time of mentoring and evaluating cadres in assessing risk factors for pregnant women using KSPR, it was found that from 21 pregnant women who visited during the activity there were 5 (23.81%) pregnant women in the high risk category (KRT) with the risk factor of pregnancy distance. (20%), history of abortion (40%), history of CS (20%) and risk factors for age >35 years (20%). Cadres have started to carry out early detection of high-risk pregnant women in Posyandu.